How ready we are? The temporary evacuation shelter (TES) and routes distance during the September 2018 earthquake based on survivor's preference - Ali, Amar Akbar; Mardin, Rifai; Yunar, Alifi; Rahman, Y A (Applied Engineering and Technology, 2023)
During Palu earthquake on September 28 2018, people in the coastline area immediately evacuates to decent heights locations. Their action preference is purely based on the aim of surviving the tsunami events. This research is aim on identify, in that conditions, how the survival chooses the TES and their route to it. This research also seeking their preference of TES and Evacuation route during the normal conditions, and compare the survival preference and what is happened during the tsunami events in September 2018. The result shows that during the tsunami disaster events, only 5 out of 74 survivals preferred evacuate to the higher buildings around the coastline within te tsunami prone area, while the others preferred to move further to the higher ground on the city centre. Majority of the survivals failed to understand the important of shortened their route as what is standard demanded.